2007
DOI: 10.1109/tsmcb.2007.907334
|View full text |Cite
|
Sign up to set email alerts
|

Idiotypic Immune Networks in Mobile-Robot Control

Abstract: Abstract-Jerne's idiotypic-network theory postulates that the immune response involves interantibody stimulation and suppression, as well as matching to antigens. The theory has proved the most popular artificial immune system (AIS) model for incorporation into behavior-based robotics, but guidelines for implementing idiotypic selection are scarce. Furthermore, the direct effects of employing the technique have not been demonstrated in the form of a comparison with nonidiotypic systems. This paper aims to addr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 21 publications
1
72
0
Order By: Relevance
“…Idiotypic systems in particular exploit Jerne's notion of an idiotypic network [7], where antibodies are capable of recognizing and being stimulated or suppressed by other antibodies via their paratopes and idiotopes, see [15] for further details. Idiotypic AIS algorithms are often based on Farmer et al's computational model [1] of Jerne's theory and are characterized by a decentralized behaviour-selection mechanism.…”
Section: Artificial Immune Systems and The Behavioural Encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Idiotypic systems in particular exploit Jerne's notion of an idiotypic network [7], where antibodies are capable of recognizing and being stimulated or suppressed by other antibodies via their paratopes and idiotopes, see [15] for further details. Idiotypic AIS algorithms are often based on Farmer et al's computational model [1] of Jerne's theory and are characterized by a decentralized behaviour-selection mechanism.…”
Section: Artificial Immune Systems and The Behavioural Encodingmentioning
confidence: 99%
“…Previous papers have provided evidence that the idiotypic AIS architecture has advantages over a reinforcement learning scheme when applied to mobile robot navigation problems [15] and have shown that the idiotypic LTL-STL architecture permits transference from the simulator to a number of different real-world environments [16]. The chief aim of this paper is, therefore, to supply further support for the robustness, scalability and adaptability of the architecture by showing that it can be extended to the much larger scale Pioneer P3-DX robots.…”
Section: Introductionmentioning
confidence: 99%
“…This paper will hence also extend the research in [2] to include a different type of robot (e-puck), more environments, different problems, the real domain, an alternative RL strategy (see section 4.4), and a variable idiotope (see section 4.2).…”
Section: Introductionmentioning
confidence: 97%
“…For example, [3]- [7] all use GAs but evolve only the network links between the antibodies, which are hand-designed, fixed, and small in number. Reference [2] also uses a fixed set of pre-engineered antibodies. In contrast, the LTL phase of this research [1] uses a GA where six basic antibody-types are encoded with a set of six variable attributes that can take many different values, meaning that the system can evolve complete sets of simple but very diverse antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used mechanisms of the biological immune response are clonal proliferation [7], negative selection [8], immune network [9], danger theory [10], and dendritic cell model [11]. Until now, AIS has been successfully applied on various complex problems, such as traveling salesman problems [12], [13], automatic clustering [14], pattern classification [15], graph drawing problems [16], mobil robot control [17], numerical optimization problems [18], and so on.…”
mentioning
confidence: 99%